ANALISIS PENGEMBANGAN BUKU CERITA BERGAMBAR BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KARAKTER SISWA SEKOLAH DASAR - Rufika, Vivin; Purwoko, Budi; Ari Metalin Ika Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to determine the application of local wisdom-based picture storybook models to improve the character of elementary school students. This research uses qualitative research methods. Researchers conducted observations, interviews, and documentation which were analyzed by reducing data, presenting data, and drawing conclusions. The results of the observations obtained, students are very enthusiastic in learning, a sense of wanting to know more about local wisdom in their own area is very high and is able to influence the character of students in learning, namely discipline, responsibility, cooperation to achieve completeness in learning, while the results of interviews with students and teachers found that they were very interested in using learning media based on Gresik local wisdom-based picture storybooks because it brings children closer to the real world, meaning that students experience in their daily lives. In other words, the development of local wisdom-based storybooks can improve the character of elementary school students.